Imbalance of Th22/Treg cells causes microinflammation in uremic patients undergoing hemodialysis - Ren, Tingting (Biosci Rep, 2019)
Background: Regulatory T (Treg) cells are of critical functionality in immune activation and inflammation in uremic patients undergoing hemodialysis (HD). A disruption in balance of Treg cells has potency to elicit infectious disease progression. Here, we examined possible association between ratio imbalance of Th22/Treg cells and microinflammation in uremic patients undergoing HD. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated to allow measurement of the percentage of Th22 cells and Treg cells using flow cytometry. Subsequently, serum levels of related cytokines, interleukin (IL) 22 (IL-22) and IL-10 and inflammatory factors, C-reactive protein (CRP), (TNF-α), IL-6 were determined via enzyme-linked immunosorbent assay (ELISA). Then relationships among dialysis time, microinflammation status (CRP) and dialysis adequacy (immunoreactive parathyroid hormone (iPTH), urea clearance index (K(t)/V), β2-MG, serum calcium, and serum phosphorus) were evaluated. Finally, correlation between microinflammation status and dialysis adequacy was analyzed with Pearson’s correlation coefficient. Results: An increased percentage of Th22 and a decreased percentage of Treg cells were evident in uremic patients undergoing HD. Serum levels of IL-22, CRP, TNF-α, and IL-6 were increased, while IL-10 serum level was reduced. An imbalance of Th22/Treg cells was associated with microinflammation status in uremic patients undergoing HD. Furthermore, prolongation of the dialysis time, the microinflammation status and dialysis adequacy were changed. Increased dialysis adequacy was observed to correlate with alleviated microinflammation of uremic patients undergoing HD. Conclusions: Conjointly, an imbalance of Th22/Treg cells may be a potential cause responsible for uremia occurrence, which in turn indicates that uremia could be effectively alleviated by altering the ratio of Th22/Treg cells.